2020
DOI: 10.5194/nhess-20-2961-2020
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationary extreme value analysis of ground snow loads in the French Alps: a comparison with building standards

Abstract: Abstract. In a context of climate change, trends in extreme snow loads need to be determined to minimize the risk of structure collapse. We study trends in 50-year return levels of ground snow load (GSL) using non-stationary extreme value models. These trends are assessed at a mountain massif scale from GSL data, provided for the French Alps from 1959 to 2019 by a meteorological reanalysis and a snowpack model. Our results indicate a temporal decrease in 50-year return levels from 900 to 4200 m, significant in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Their accuracy on the mesoscale is significantly enhanced thanks to fine spatial sampling, and improved representation of: soil atmosphere interactions, orographic effects, land-use effects, and land-ocean contrasts [23]. Reanalysis of weather data (precipitation, temperature, humidity, radiation, and wind speed) can also be used to run snowpack models and derive snow water equivalent data [47,48].…”
Section: Reanalysis Datasetmentioning
confidence: 99%
“…Their accuracy on the mesoscale is significantly enhanced thanks to fine spatial sampling, and improved representation of: soil atmosphere interactions, orographic effects, land-use effects, and land-ocean contrasts [23]. Reanalysis of weather data (precipitation, temperature, humidity, radiation, and wind speed) can also be used to run snowpack models and derive snow water equivalent data [47,48].…”
Section: Reanalysis Datasetmentioning
confidence: 99%
“…On the other hand, climate projections for the Pyrenees and the Alps under a high greenhouse gas emission scenario (SRES A2 and RCP8.5, respectively) show that the mean seasonal maximum of snowfall is expected to decrease below a transition elevation and increase above it. López-Moreno et al (2011) estimated a transition elevation of around 2000 m for the Pyrenees (comparing 2070-2100to 1960-1990), while Frei et al (2018 estimated a transition of around 3000 m for the Alps (comparing 2070Alps (comparing -2099Alps (comparing to 1981Alps (comparing -2010. In the French Alps, despite the existence of sufficient snowfall records and of previous studies that exploited them in an explicit extreme value framework, temporal trends in extreme snowfall remain poorly described.…”
Section: Introductionmentioning
confidence: 99%
“…Recent collapses of large-span lightweight roofs [6,7,[16][17][18] confirmed that extreme snow loads can cause significant economic damages and causalities [19]. A discussion about the reliability and failure of roofs subjected to snow loads can be found in [20] where a total of 249 roof collapses during the winter 2005/2006 is investigated identifying main observed causes into human errors and insufficient code provisions.…”
Section: Introductionmentioning
confidence: 99%